Islamic Higher Education Financing Management: An NVivo-Based Qualitative Study at Universiti Teknologi Malaysia - Sangkot Abdullah Efendi Harahap; Sulikah; Yundri Akhyar; M Tholibin Azhari; Mukhtar Latif; M. Syahran Jailani (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study examines the management of Islamic higher education financing at Universiti Teknologi Malaysia (UTM) using an NVivo-based qualitative approach. The data were analyzed through Word Cloud, Tree Map, Hierarchy, and Project Map techniques to identify patterns and structures within the funding system. The findings indicate that UTM’s financing framework is shaped by a combination of government funding and Islamic endowment mechanisms, with instruments such as zakat, waqf, cash waqf, and donations serving as the dominant non-governmental sources. Scholarship schemes emerge as the primary distribution mechanism, covering merit-based aid, financial-need support, and funding for research and internationalization programs. Principles of social justice and maqasid al-shariah play a crucial role in guiding the allocation of resources, particularly for students from lower socioeconomic backgrounds. The study concludes that UTM’s financing model is holistic and sustainability-oriented, and recommends strengthening the governance of Islamic endowments, diversifying scholarship schemes, and enhancing policy synergies between the government and Islamic philanthropic entities.